Language and Color Perception: Evidence From Mongolian and Chinese Speakers - He, Hu; Li, Jie; Xiao, Qianguo; Jiang, Songxiu; Yang, Yisheng; Zhi, Sheng (Frontiers in Psychology, 2019)
The present research contributes to the debate in cognitive sentence on the relationship between language and perception by comparing Mongolian and Chinese speakers’ color perception. In this study, featuring a free sorting task and a visual search task comparing Mongolian and Chinese performances, the results show that both universal and relativistic forces are at play. Chinese (Mandarin) and Mongolian color terms divide the blue spectrum differently but the green spectrum, similarly. In Mongolian, light blue (“qinker”) and dark blue (“huhe”) are strictly distinct, while both light green and dark green are described as one word, nogvgan. In Chinese, however, both light blue and dark blue are simply described by one word, lan, and both light green and dark green are described by a single word, lv. The current study used a free-sorting task and a visual search task to investigate whether this linguistic difference between Chinese and Mongolian speakers leads to a difference in color discrimination. In the free-sorting task, compared with Chinese speakers, Mongolian speakers exhibited different sorting in the blue region (by distinguishing light and dark blue) and the same sorting in the green region. Further results showed that Mongolian speakers discriminated visual search displays that fall into different linguistic categories in Mongolian (e.g., qinker or huhe) more quickly than visual search displays that belong to the same linguistic category (e.g., both qinker) in a visual search task. Moreover, this effect was disrupted in Mongolian participants who performed a secondary task engaging involving verbal working memory (but not a task engaging involving spatial working memory), suggested linguistic interference. Chinese (Mandarin) speakers performing the visual search task did not show such a category advantage under any of the conditions. The finding provides support for the Whorf hypothesis with evidence from an Altay language. Meanwhile, both Chinese and Mongolian speakers reacted faster to the green color than the blue color in the visual search task, suggesting that the variation in human color perception is constrained by certain universal forces. The difference in categorical effects between Chinese and Mongolian speakers in the blue region suggests a relativistic aspect of language and color perception, while the speed of visual search in blue and green suggests a universalistic aspect of language and color perception. Thus, our findings suggest that our perception is shaped by both relativistic and universal forces.